Improving English education in Japan, with an emphasis on promoting communication skills in elementary schools : inspiration from the Icelandic national curriculum - Sherine Otomo 1993- (2018)
This thesis focuses on improving Japanese pupils’ English communication skills by examining the current Japanese curriculum from a perspective that reconsiders the teaching methods employed and emphasizes internationalizing the classroom. There are three main reasons for the writing of this thesis: First, English education has long been an interest of the author. Second, living as a Japanese student in Iceland for the past few years (and having spent one year in England) has brought about a certain awareness on the author’s part of the extremely low level of English ability in Japan; this is particularly apparent in comparison to Icelandic students’ high performance in English. Third, Japan is experiencing a wave of rapid globalization as a result of preparing for the 2020 Olympic Games. These reasons represent the main motives for reconsidering English education in the author’s home country, Japan, by writing this thesis. The paper conducts a literature review in order to examine the current Japanese curriculum and to present a comparison of the Japanese and the Icelandic curricula. The existing Icelandic curriculum has an excellent policy structure which identifies teaching objectives and the recommended teaching method. It serves as an inspiring source of comparison and provides ideas for improving the Japanese curriculum. This paper focuses on the following two research questions: 1. What are the differences between the Japanese and the Icelandic national curricula in terms of teaching methods and internationalization? 2. What can be learned from the Icelandic national curriculum concerning the communicative approach and internationalization, and how could such findings be adopted in the Japanese national curriculum in order to improve students’ communication skills in English? The first chapter examines English education in Japan and identifies the problems currently affecting it; furthermore, it introduces the current Japanese curriculum. The second chapter examines the Icelandic national curriculum with ...